3D nanoscale elemental mapping of precipitates in steel: Evaluation of analytical electron tomography and comparison to atom probe tomography. (May 2022) - Trummer, Cornelia; Mendez-Martin, Francisca; Kothleitner, Gerald; Haberfehlner, Georg
Abstract: To identify different types of precipitates and their composition, analytical electron tomography analysis on a needle-shaped sample was performed. Three-dimensional chemical maps from each element in a high alloyed steel are acquired and the resulting elemental maps are jointly reconstructed. Since analytical electron tomography data suffers from noise, total generalized variation regularization is used to improve the reconstruction quality compared to conventional reconstruction techniques. We analyse the influence of regularization parameters on these reconstructions in terms of elemental quantification, and compare these results to atom probe tomography measurements done on another sample of the same material. Highlights: The impact of reconstruction parameters on elemental quantification in analytical electron tomography is investigated. Elemental quantification from analytical electron tomography is compared to atom probe tomography. Routes to choosing adequate reconstruction parameters are highlighted.